Keynes on population - Toye, John (Oxford Oxford University Prees, 2000)
The topic of population is treated in modern biographies of John Maynard Keynes. Keynes Neo-Malthusianism views on population, is based on a postulated link between population growth and deteriorating terms of trade. This led him to take up a militant sta
Keywords: Keynes,John Maynard,1883-1946-View on population; Population; Demography malthusianism; Population-Economic aspects